2020
DOI: 10.1002/ppul.24760
|View full text |Cite
|
Sign up to set email alerts
|

Lung ultrasound: A useful additional tool in clinician's hands to identify pulmonary atelectasis in children with neuromuscular disease

Abstract: Introduction and ObjectivesPatients with neuromuscular disease (NMD) are often exposed to ionizing radiations which could be reduced if a noninvasive and reliable diagnostic method is identified. The major aim of this study was to compare the use of chest X‐ray (CXR) with lung ultrasound (LUS) in pediatric patients with NMD, to identify pulmonary atelectasis (PA).Materials and MethodsA prospective study was conducted on children affected by NMD. In all patients who underwent CXR, a LUS was also performed and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…Ultrasound has unique advantages in the diagnosis of pulmonary atelectasis, and has become an important tool for the diagnosis of pulmonary atelectasis because of its convenience, noninvasiveness, high accuracy, and lack of radiation damage. It is also possible to visualize, in real time and in a dynamic state [20]. The resuscitation maneuver reverses the atelectasis and significantly improves pulmonary gas exchange.…”
Section: Discussionmentioning
confidence: 99%
“…Ultrasound has unique advantages in the diagnosis of pulmonary atelectasis, and has become an important tool for the diagnosis of pulmonary atelectasis because of its convenience, noninvasiveness, high accuracy, and lack of radiation damage. It is also possible to visualize, in real time and in a dynamic state [20]. The resuscitation maneuver reverses the atelectasis and significantly improves pulmonary gas exchange.…”
Section: Discussionmentioning
confidence: 99%
“…A study of 40 children with neuromuscular disease showed an excellent agreement between atelectasis on POCUS by either a radiologist or pediatrician with experience in this modality and CXR as interpreted by a radiologist, with the qualification that clinical correlation is required in the not infrequent case of an inconclusive result. 27 A study of 80 intubated neonates in intensive care, using expanded criteria for the sonographic diagnosis of atelectasis, showed a higher sensitivity for atelectasis on lung ultrasound than on CXR, using CT as a gold standard when CXR was normal. 28 Last, a study of 15 pediatric patients anesthetized for MRI showed 88% accuracy when comparing lung ultrasound for atelectasis with MRI, with high interrater reliability for both modalities.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, LUS had a better inter-reader agreement for all the mentioned signs [62]. Other diseases that showed non-specific LUS findings are sickle cell disease [64], scoliosis [65], anomalous origin of left coronary artery from the pulmonary artery (ALCAPA) [66], acute asthma [67], interstitial lung diseases [68], neuromuscular diseases [69] and cystic fibrosis [70,71]. A case series of four patients with severe scoliosis showed that LUS could be useful to detect lung consolidation in these patients when CXR is hampered by costal deviations [65].…”
Section: Lus In Bronchiolitis Pneumothorax and Other Paediatric Respiratory Diseasesmentioning
confidence: 99%